Enhanced control of single-molecule emission frequency and spectral diffusion - Duquennoy, Rocco; Landrieux, Simon; De Bernardis, Daniele; Mony, Juergen; Colautti, Maja; Jin, Lin; Pernice, Wolfram; Toninelli, Costanza (ACS nano, 2024)
The Stark effect provides a powerful method to shift the spectra of molecules, atoms, and electronic transitions in general, becoming one of the simplest and most straightforward ways to tune the frequency of quantum emitters by means of a static electric field. At the same time, in order to reduce the emitter sensitivity to charge noise, inversion symmetric systems are typically designed, providing a stable emission frequency with a quadratic-only dependence on the applied field. However, such nonlinear behavior might be reflected in correlations between the tuning ability and unwanted spectral fluctuations. Here, we provide experimental evidence of this trend using molecular quantum emitters in the solid state cooled down to liquid helium temperatures. We finally combine the electric field generated by electrodes, which is parallel to the molecule’s induced dipole, with optically excite long-lived charge states acting in the perpendicular direction. Based on the anisotropy of the molecule’s polarizability, our two-dimensional control of the local electric field allows us not only to tune the emitter’s frequency but also to sensibly suppress the spectral instabilities associated with field fluctuations.